2014
DOI: 10.1111/jdv.12820
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery – a dermatologic perspective

Abstract: Bariatric surgery has become a standard option in morbid obesity for patients not responding to conventional treatment. A major and stable weight loss can be achieved. Since obesity and weight loss may affect skin diseases, we performed this review to analyse the impact of bariatric surgery on a number of skin diseases. We categorized the skin diseases into three main groups: (i) diseases with a possible benefit from bariatric surgery, (ii) diseases that may develop after bariatric surgery and (iii) diseases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
9
0
3
Order By: Relevance
“…Bariatric surgery is an invasive method to treat patients with morbid obesity. Even after successful bariatric surgery, lipedema has been documented in patients not responding with the overall weight loss (Bast, Ahmed, & Engdahl, ; Wollina, Dreßler, & Lohmann, ).…”
Section: Adipose Tissuementioning
confidence: 99%
“…Bariatric surgery is an invasive method to treat patients with morbid obesity. Even after successful bariatric surgery, lipedema has been documented in patients not responding with the overall weight loss (Bast, Ahmed, & Engdahl, ; Wollina, Dreßler, & Lohmann, ).…”
Section: Adipose Tissuementioning
confidence: 99%
“…It has been shown that significant weight loss after BS does indeed improve the systemic inflammatory state associated with the MetS, modulating the release of pro‐inflammatory cytokines, C‐reactive protein and adipokines . However, BS has been associated with various cutaneous complications, which can be broadly classified as direct cutaneous adverse effects (AEs), such as acquired skin laxity and delayed wound healing, and indirect cutaneous AEs, resulting from effects on the nutritional status and on the onset/course of concomitant inflammatory immune‐mediated skin diseases . In HS, which is a low‐prevalence, orphan skin disease, there are limited data on the clinical outcomes of weight‐loss interventions.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, BS has been associated with various cutaneous complications, which can be broadly classified as direct cutaneous adverse effects (AEs), such as acquired skin laxity and delayed wound healing, and indirect cutaneous AEs, resulting from effects on the nutritional status and on the onset/course of concomitant inflammatory immune-mediated skin diseases. 11 In HS, which is a low-prevalence, orphan skin disease, there are limited data on the clinical outcomes of weight-loss interventions. In a single retrospective study, a restrictive BS intervention was reported to induce an improvement of disease activity in > 50% of patients with established HS.…”
Section: Discussionmentioning
confidence: 99%
“…Tatsächlich können bestimmte Patienten mit Hauterkrankungen wie Hidradenitis suppurativa, Intertrigo oder Psoriasis, die mit einem hohen BMI assoziiert sind, von einem bariatrischen Eingriff profitieren. Andererseits haben verschiedene Mangelsyndrome wie erworbene Acrodermatitis enteropathica, Phrynoderm oder Skorbut schwerwiegende Folgen, besonders bei Patienten, die sich chirurgischen Verfahren unterzogen haben, welche zur Malabsorption führen . Da jedoch die meisten Mangelzustände subklinisch sind, treten dermatologische Manifestationen selten auf, und uns sind keine umfassenden Studien bekannt, in denen Risikofaktoren für Hautsymptome einer Mangelernährung bei Patienten mit einer bariatrischen Operation in der Vorgeschichte identifiziert worden wären .…”
Section: Einführungunclassified